A Health System's Preparedness for the "Next Ebola". Issue 1 (January 2018) - Baers, Justin H.; Wiley, Katelyn; Davies, J. M.; Caird, Jeff K.; Hallihan, Greg; Conly, John
We share lessons learned from a collaborative in situ simulation of Ebola preparedness for a large health region. The lessons are to use proactive analysis, undertake in situ simulation, and have professionals in infection prevention and control and those in human factors collaborate. These lessons are applicable as generalizable concepts, not only to Ebola preparedness but also to other infectious diseases, including the "next Ebola." Implementing these concepts will help contribute to improvements in both patient and provider safety.